Prevalence of secondary arterial hypertension in patients with acute renal failure in a secondary-level pediatric hospital in Northwestern Mexico - Humberto Peña-Guevara; Iyali M. Corrales-Cambero; Saúl Cañizales-Muñoz (Permanyer, 2024)
Background: The worldwide prevalence of arterial hypertension in pediatric patients is 3.5%, and it has repercussions at renal, cardiovascular, neurological, and lifestyle levels. This study aimed to estimate the prevalence of arterial hypertension, mortality, and follow-up in patients with acute renal failure in the nephrology outpatient clinic at a second-level hospital in Northwestern Mexico. Methods: We conducted a descriptive, retrospective, and observational study. Men and women aged 1-18 years diagnosed with acute kidney injury were analyzed from January 1, 2012, to December 31, 2021. The medical and electronic records of the candidate patients were analyzed, and nutritional data, laboratory analysis, most frequent etiology, and follow-up in the pediatric nephrology clinic were collected. Those with exacerbated chronic kidney disease and previous diagnosis of high blood pressure were excluded. Results: One hundred and seventy-four patients were evaluated, and only 40 were eligible for the study (22.98%), predominantly males with a mean age of 9.9 years. The degree of arterial hypertension was 50% for grade I and 50% for grade II (p = 0.007); the mortality rate was 32%. One hundred percent of hypertension cases were controlled at 6 months after discharge (p = 0.000080). Conclusions: Our results were similar to those reported in other studies. Follow-up and early detection of arterial hypertension in children need to be strengthened.